Peningkatan aktivitas dan hasil belajar bahasa indonesia pada materi teks deskripsi melalui metode mind mapping siswa kelas VII MTsS Krueng Raya - Badriah, Badriah (Jurnal Pendidikan dan Pengabdian Vokasi (JP2V), 2020)
The purpose of this study is to improve the activities and learning outcomes of Indonesian Language in the Description Text material of Grade VII students of MTsS Krueng Raya. The learning method used in this study is Mind Mapping. The subjects of this study were Grade VII students of MTsS Krueng Raya. The number of students is 25 students with 12 male students and 13 female students. This research was conducted in the 2019/2020 school year within a period of 3 months namely from August 2019 to Octo-ber 2019 in the odd semester. The methodology of this research is Classroom Action Research (CAR) consists of two cycles and each cycle consists of two meetings. In each cycle consists of planning, im-plementation, observation and reflection. Data collection technique is to collect the value of the test car-ried out at the end of each learning in each cycle by using the question instrument (written test). Obser-vation data is done by looking at the activeness of students in the learning process. Data were analyzed by means of percentage statistics. The results showed that an increase in student learning activities in both cycles, from the category of being good enough and the good category increasing to very good. Completeness of student learning outcomes has increased from 44% in the pre cycle increased to 68% in the first cycle and increased to 88% in the second cycle. The use of the Mind Mapping Method can im-prove Indonesian learning activities and outcomes in the Description Text material of Grade VII students of MTsS Krueng Raya Academic Year 2019/2020.